Enhancing pathogens detection in suspected geriatric bloodstream infections using Nanopore-targeted sequencing - Menghui Zhao; Yan Ouyang; Junchi Mei; Hang Liu (Microbiology Spectrum)
ABSTRACT Bloodstream infections (BSIs) are a critical concern for elderly patients, where prompt and accurate diagnosis is vital for effective treatment. Traditional blood culture methods suffer from delayed results and susceptibility to false-negatives. Nanopore-targeted sequencing (NTS) offers rapid pathogen detection and reporting, presenting a promising alternative. However, the application of NTS for diagnosing suspected BSIs in geriatric patients remains insufficiently studied. We conducted a retrospective cohort study from January 2022 to January 2024, including 198 geriatric patients suspected of BSIs. We utilized NTS to detect pathogen characteristics and compared the effectiveness and consistency of NTS with simultaneous blood culture testing for pathogen detection. NTS demonstrated a pathogen detection rate of 61.1%. The most common bacterial pathogens were Escherichia coli and Staphylococcus aureus (each 7.7%), while Candida albicans was the most prevalent fungal pathogen (30%). Mixed-bacterial infections were detected in 21.7% of NTS-positive cases, and concurrent bacterial–fungal infections were observed in 9.92% of these cases. NTS-positive patients had higher rates of comorbidities, elevated inflammatory markers, and worse prognoses compared to NTS-negative patients. NTS exhibited a significantly higher pathogen detection rate and faster turnaround time than blood culture (78.1% vs 42.2%, P < 0.001), with an agreement rate of 65.6%. The elderly BSI patients frequently involve multiple or mixed infections and correlate with poorer prognoses. NTS provides a faster and more sensitive diagnostic alternative to traditional blood culture, potentially improving clinical outcomes and guiding more effective treatment strategies. This study highlights the need for further research to validate the routine clinical integration of NTS for managing BSIs in geriatric populations.IMPORTANCEBloodstream infections (BSIs) in elderly patients pose substantial diagnostic and therapeutic challenges due to the limitations of traditional blood culture methods, which are hampered by slow turnaround times and false-negatives. Nanopore-targeted sequencing (NTS) emerges as a significant advancement, offering rapid and accurate pathogen detection directly from blood samples. This study demonstrates that NTS provides a higher detection rate and faster results than conventional blood cultures, crucial for the timely management of BSIs in geriatric patients, who often present with multiple or mixed infections and have poorer clinical outcomes. The findings underscore the potential of NTS to enhance diagnostic accuracy and speed, informing more effective treatment strategies and improving overall patient outcomes. Further research is essential to establish NTS as a routine diagnostic tool in the clinical management of BSIs in the elderly.